The answer
f(x) = 0.7(6)x = <span>f(x) = 0.7(6)^x, and </span><span>g(x) = 0.7(6)–x= </span>g(x) = 0.7(6)^-x=1/<span>0.7(6)^x
so </span>
g(x) =1/<span>0.7(6)^x=1 /</span><span><span>f(x)
</span> the relationship between f and g are </span>g(x) =1 /<span>f(x) or </span><span>g(x) . <span>f(x) = 1</span> </span>
Answer:
90,30
Step-by-step explanation:
let the three times be 3x then,
3x-22=68
3x=68+22
3x=90
x=90/3
x=30
again,
3x=3*30=90
please support me and give me brainliest
Two and one eighth is the answer
Answer:
C
Step-by-step explanation:
Well, anything multiplied by zero is zero.
If you multiplied 0 by 143, you wouldn't get anything because you're not multiplying with another number that can be multiplied by.
Answer:
(1,-1)
Step-by-step explanation:
If you try plugging in the numbers for x in the equation y > Ix + 1I - 1, you'll find the answer.